Association between the duration of smart phone use and back dysfunction in patients with chronic mechanical low back pain - Mina Magdy Wahba Nasrallah; Aliaa Rehan Youssef; Dina Othman Shokri Morsi Galal (Cairo : Mina Magdy Wahba Nasrallah, 2019)
Background: Excessive smart phone use has been associated with pain in the upper quadrant, however, the relationship between usage duration and low back pain (LBP) is still unclear. Objective: This study aimed at investigating the association between continuous smart phone use for game playing up to 30 minutes and changes in back pain and proprioception acuity in patients with chronic mechanical LBP. Methods: Fifty-six patients with chronic mechanical LBP played a game while seated in two separate sessions; either for 10- or 30-minutes. In each session, pain and the angle of back repositioning error were measured at baseline and immediately after game playing using the visual analogue scale and the Biodex isokinetic dynamometer system 3, respectively. Results: Immediately after smart phone use, pain significantly increased compared to baseline values, regardless to the duration (p<0.05). However, the changes in perceived pain scores between baseline and post-playing scores were not significantly different between the two tested durations (p>0.05). The angle of repositioning error was not significantly different within the same testing session nor between the two durations tested (p>0.05)
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Musculoskeletal Disorders
Issued also as CD
Keywords: Chronic low back pain; Proprioception; Smart phone